IMPLEMENTASI KEBIJAKAN PENGELOLAAN KEBERSIHAN DI KECAMATAN MALALAYANG KOTA MANADO - Pinatik, Levin Philips (JURNAL ADMINISTRASI PUBLIK, 2018)
The purpose of this study is to explain the process of implementing hygiene managementpolicies in Malalayang sub-district, Manado. This study uses a qualitative descriptive method, which is toexplain or describe descriptively about how and why various variants or factors related to theimplementation of hygiene management policies in Malalayang sub-district.The results showed that 1.The enactment of the Mayor of Manado regulation No. 13 of 2016 concerning the delegation of authorityover hygiene management to the Malalayang sub-district of Manado City, when viewed from aspects ofstandard policies and targets, resources, communication, characteristics, social, economic, political andaspects of involvement attitudes or dispositions are appropriate and appropriate application indicated bythe results of interviews of all informants who argued that the level of perception was good and satisfiedwith the performance of the Malalayang District government along with its staff in hygiene management,2. Implementation of hygiene management policies in Malalayang sub-district when viewed from fiveaspects namely policy standards and targets, communication, characteristics, involvement of the social,economic, political environment as well as aspects of attitudes or dispositions, the implementation hasbeen effective and good, but when viewed from the aspect of resources, management of cleanliness is stillfelt to be not efficient enough from in terms of the time of completion and still not suitable as expected tocompensate for the large volume of waste produced, due to the limited resources available such as: theneed for additional facilities for garbage transportation vehicles and daily freelancers (THL), there arestill long distances for every facility and infrastructure for hygiene management in urban villages.Keywords: Policy Implementation, Hygiene, Management.